MHC and kin discrimination in juvenile Arctic charr, Salvelinus alpinus (L.) - Olsen, K. H.; Grahn, Mats; Lohm, Jakob; Langefors, Åsa (Animal Behaviour, 1998)
Kin recognition and discrimination ale thought to occur in several species of various taxonomic groups. In salmonid fish, juveniles can discriminate between odours of siblings and nonsiblings from the same population even if the odour donors and the test fish have been reared separately since fertilization. This indicates that some genetic factor is important in the recognition process. The mechanisms behind kin recognition and discrimination have not yet been described. In the present study, we performed fluviarium tests to examine whether kin recognition and discrimination in juvenile Arctic charr are influenced by the major histocompatibility complex (MHC). Prior to the fluviarium tests, exon 2 of an MHC class II B gene in charr was analysed with denaturing gradient gel electrophoresis (DGGE) and individual genotypes were determined. In the fluviarium, when fish had the choice between water scented by an MHC identical sibling: and a sibling with a different MHC genotype they preferred water from identical siblings. Moreover, water scented by an MHC different sibling was preferred to water from an MHC different nonsibling. However, we observed no discrimination when the test fish shared one allele with the nonsibling donor but no alleles with the sibling donor. Our results indicate that the MHC has a significant influence on the odours used for kin recognition and discrimination in juvenile Arctic charr. (C) 1998 The Association for the Study of Animal Behaviour.